Imam Ibn Marzug -the grandson- and his contributions to jurisprudence and its origins - Baadji, Abdelatif; Madjidi, Manaa (International Journal of Psychosocial Rehabilitation, 2022)
This study aims to clarify the status of Imam Ibn Marzug, the grandson, among the hardworking scholars, and to shed light on his scientific effects, especially in jurisprudence and fundamentals, and to reveal the printed and manuscript ones, by answering the problem posed about his scientific status, and the extent of his contribution to the jurisprudential and fundamentalist lesson.For the purpose of completing the study, we followed the descriptive approach, taking advantage of analysis and comparison mechanisms.We divided the study into two sections: the first is for a brief translation about the life of Imam Ibn Marzug, and his most famous sheikhs and students.The second was to explain his most important works on jurisprudence and fundamentals. In conclusion, we concluded that Imam Ibn Marzug, the grandson, is a mujtahid of the Maliki school of thought, who enriched the scientific library with many books, most of which are still in manuscript.